Retention of an ingested small blunt foreign body - K C Ng (Journal of the Belgian Society of Radiology, 2011)
Foreign body ingestion is a common problem in clinical practice. Majority of foreign bodies, once passed beyond the stomach, will be evacuated through the gastrointestinal tract within days without any difficulty. Retained foreign body is rare and the objects in question are mostly long, large, or have a sharp end. We report a case of retention of a small, blunt, spherical glass-like object in the ileum of an 87-year-old lady having benefited from a Hartmann’s procedure which was incidentally discovered on a computed tomography scan 2 months before its spontaneous evacuation through the stoma.